097 Disability and quality of life changes in people with MS (pwMS) throughout the COVID-19 pandemic. Issue 6 (27th May 2022) - Rodgers, William; Middleton, Rod; Witts, James; Lumicisi, Brooke; Nicholas, Richard
Abstract : Introduction: The UK MS Register (UKMSR) has collected longitudinal patient reported outcomes (PROs) on pwMS regularly since 2011. Aim to assess changes in disability and quality in life (QOL) in the UKMSR before and during the pandemic Methods pwMS who answered the PROs: webEDSS to assess disability in MS and EQ5D-3L visual analogue scale for QOL, six months prior to the pandemic (t-6), at the start (t0), and six months after (t+6). Results: 1553 pwMS completed QOL assessment. Of the 458 who started with a lower QOL (<50) there was improvement at t0 which stabilised at t6 (t-6=34, t0=40, t6+=39, x2=89.91, p<0.001). In those starting with a QOL ³50 their QOL worsened at the start of the pandemic (t-6=75, t0/t+6=71, x2=58.28, p<0.001). webEDSS scores were completed by 902 pwMS. There was no change in 501 pwMS with an initial webEDSS ³6.0. In 401 pwMS with a webEDSS score <6 there was a worsening in median score at t0 but not then at t6 (t-6=3.0, t0/t+6=3.5, x2=21.57, p<0.001), QOL also worsened in a similar pattern in this group. Conclusion: Disability and QOL worsened in those doing better at the start of the pandemic. Whereas in those more significantly affected, disability remained stable and QOL improved. r.m.middleton@swansea.ac.uk